2010
DOI: 10.1002/ejoc.200900905
|View full text |Cite
|
Sign up to set email alerts
|

Keronopsamides, a New Class of Pigments from Marine Ciliates

Abstract: New pigments with an unprecedented skeleton, named keronopsamides A-C, were isolated from the marine ciliate Pseudokeronopsis riccii. The structure of the most abundant secondary metabolite, keronopsamide A, was established through extended Nuclear Magnetic Resonance (NMR) analysis and mass spectrometric (MS) data obtained by using electrospray (ESI) and matrix assisted laser desorption (MALDI) ionizations. Structures of the minor analogues (keronopsamide B and C) were inferred from 1 H NMR, chemical correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
(17 reference statements)
0
17
0
Order By: Relevance
“…Particularly in P. carnea [64] and in P. erythrina [65], these granules are reported as extrusive organelles. New secondary metabolites, keronopsins and keronopsamides, respectively, produced by P. rubra and P. riccii, were recently isolated together with their sulfate esters (Figure 14) [66,67]. In the case of P. rubra, it was demonstrated that a crude extract of this organism containing keronopsins, A1 and A2, and their sulfate esters B1 and B2, is capable of paralyzing or even killing ciliates and flagellates [66].…”
Section: The Chemical Defensementioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in P. carnea [64] and in P. erythrina [65], these granules are reported as extrusive organelles. New secondary metabolites, keronopsins and keronopsamides, respectively, produced by P. rubra and P. riccii, were recently isolated together with their sulfate esters (Figure 14) [66,67]. In the case of P. rubra, it was demonstrated that a crude extract of this organism containing keronopsins, A1 and A2, and their sulfate esters B1 and B2, is capable of paralyzing or even killing ciliates and flagellates [66].…”
Section: The Chemical Defensementioning
confidence: 99%
“…For these reasons a defensive function for these secondary metabolites has been proposed; however, no data relative to their cellular localization and mechanism of action are available to date. On the other hand, in the case of P. riccii, the function of the alkaloid secondary metabolite keronopsamide A and its sulfate esters B and C has not been investigated, and the possible localization of the pigments in the cortical granules is only presumed [67]. The most extensively studied species is P. erythrina; previously described as an estuarine one, it was successively found also in the freshwater environment and hence reported as a euryhaline organism [68].…”
Section: The Chemical Defensementioning
confidence: 99%
“…In other studies, the secondary metabolites produced by a ciliate were simply analyzed after rough cell extractions, generally using organic solvents. However, through this procedure, information about the original cell localization of the analyzed substances was lost and not always deducible .…”
Section: Quantitative Effect On the Number Of Extrusome‐deprived Cellmentioning
confidence: 99%
“…Keronopsamides are likely to occur from 3-bromotyrosine and pyrrole propenoic acid. Guella et al, 2010b …”
Section: Keronopsins and Keronopsamides Of Pseudokeronopsis Rubra Andmentioning
confidence: 99%